Relevansi Pendidikan Karakter dalam Al-Qur’an Sebagai Pembentuk Kepribadian - Husaini, Husaini; Salis, Rizkoni (P3M POLITEKNIK NEGERI AMBON, 2023)
Character education is a process of formation and habituation in a systematic or directed manner so that humans have character, character, psychological traits, manners, personality, and morals in accordance with the rules, norms and values that have been applied or agreed upon in society, religion and the state. While the Qur'an is discussed to describe the relevance of character education which is widely stated, especially in surah Luqman verses 13-19 as a personality builder. The purpose of this research is for people to know that character education which is a guide in life is in line with the Qur'an so that people emphasize the character that forms a good personality based on religious teachings to be applied to life. This study uses a qualitative approach. The method used in this study is the reference search method or literature study. The results of this study indicate the relevance of character education which can be found in surah Luqman verses 13-19 as forming personality which includes: being grateful to Allah SWT, devoted to both parents, caring attitude to help and help, Commands to do what is ma'ruf (good) and prevent those who are Munkar (bad), be patient, don't be arrogant, and don't be arrogant.Keywords: character education, al-Qur'an surah Luqman verses 13-19, forming personality